(untitled) (REMUNOM, 2026)
This article analyzes the relationship between teacher education and curriculum in the context of full-time education in Brazilian public schools, considering the theoretical foundations, normative frameworks, and pedagogical challenges that affect its implementation as an educational policy. The study is grounded in the understanding that the extension of the school day, in itself, does not ensure the qualification of educational processes, requiring the reorganization of teaching work, curriculum structures, and institutional conditions within schools. The research is characterized as bibliographic and documentary, adopting a qualitative approach based on the analysis of scientific articles, dissertations, theses, and legal documents published mainly from the 2000s onward. The discussion examines the main normative instruments that guide full-time education in Brazil, with emphasis on the National Education Guidelines and Framework Law, the National Education Plans for the periods 2001–2010 and 2014–2024, and the More Education Program, the Program for Fostering Full-Time Upper Secondary Schools, and the Full-Time School Program, analyzing their implications for initial and continuing teacher education. The analysis indicates that, despite normative and quantitative advances in the expansion of full-time education, significant weaknesses persist in the articulation between extended school time, curriculum organization, and teacher education policies. The results suggest that the lack of specific training guidelines, institutional time allocated for collective planning, and adequate working conditions tends to limit the pedagogical potential of extended school hours, often resulting in the maintenance of traditional teaching practices within a longer school day. It is concluded that consolidating full-time education as a public policy requires continuous investment in teacher education, curriculum reorganization, and the professional recognition of teachers, in order to ensure integrated, socially grounded, and pedagogically coherent educational practices.